# 勒让德定理

## 证明

{\displaystyle {\begin{aligned}\nu _{p}(n!)&=n_{1}+2n_{2}+3n_{3}+...=\sum _{r\geq 1}rn_{r}\\&=(n_{1}+n_{2}+n_{3}+...)+(n_{2}+n_{3}+...)+(n_{3}+...)=N_{1}+N_{2}+N_{3}+...=\sum _{k\geq 1}N_{k}\end{aligned}}}

## 其它表達式

${\displaystyle \nu _{p}(n!)={\frac {n-s_{p}(n)}{p-1}}.}$

### 證明

${\displaystyle n=n_{\ell }p^{\ell }+\cdots +n_{1}p+n_{0}}$

${\displaystyle \textstyle \left\lfloor {\frac {n}{p^{i}}}\right\rfloor =n_{\ell }p^{\ell -i}+\cdots +n_{i+1}p+n_{i}}$

{\displaystyle {\begin{aligned}\nu _{p}(n!)&=\sum _{i=1}^{\ell }\left\lfloor {\frac {n}{p^{i}}}\right\rfloor \\&=\sum _{i=1}^{\ell }\left(n_{\ell }p^{\ell -i}+\cdots +n_{i+1}p+n_{i}\right)\\&=\sum _{i=1}^{\ell }\sum _{j=i}^{\ell }n_{j}p^{j-i}\\&=\sum _{j=1}^{\ell }\sum _{i=1}^{j}n_{j}p^{j-i}\\&=\sum _{j=1}^{\ell }n_{j}\cdot {\frac {p^{j}-1}{p-1}}\\&=\sum _{j=0}^{\ell }n_{j}\cdot {\frac {p^{j}-1}{p-1}}\\&={\frac {1}{p-1}}\sum _{j=0}^{\ell }\left(n_{j}p^{j}-n_{j}\right)\\&={\frac {1}{p-1}}\left(n-s_{p}(n)\right).\end{aligned}}}